Development of Local Wisdom-Based Animated Videos to Introduce Buol Cultural Values - Virna, Sri; Zuama, Shofiyanti Nur; Awalunisah, Sita; Agusniatih, Andi (FKIP - Universitas Riau, 2025)
Introduction to culture is believed to be one of the important learning contents for early childhood because it is part of the foundation of the formation of a child's identity. Introduction to culture also becomes more relevant and important to prepare children as members of society and their culture in the development period. This type of research uses the type of development research or Research and Development (R&D). The development research in this study is to produce an animated video media based on local wisdom. The learning media developed aims to be an alternative media in introducing Buol cultural values to children. This development research was conducted to produce an animated video media product based on local wisdom in introducing Buol cultural values to early childhood, where this research was only conducted in Group B of Aba XVII Kindergarten, Matinan Village, Gadung District. The application of Local Wisdom-Based Animated Videos in Introducing Buol Crocodile Values applied in this study is to introduce Local Wisdom-Based Animated Videos in Introducing Buol Cultural Values to students. Introducing Buol culture that will be introduced to children, asking children whether they have ever seen Buol culture as shown in the video slide.